The Effect of Land Use on Carbon Stocks and Implications for Climate Variability on the Slopes of Mount Elgon, Eastern Uganda - Mugagga, F.; Nagasha, B.; Barasa, B.; Buyinza, M. (International Journal of Regional Development, 2017)
We investigated the impact of land use change on carbon stocks and its implications to climate variability in Mountain environments. Remotely sensed biophysical data was used to determine the extent of land use change over the last two decades. Land uses were stratified thus; forest under restoration, woodlots/plantations, agricultural land, regenerating forest and intact forest. Carbon in above and below ground biomass was measured using the allometric equations, whilst soil samples were analyzed for total carbon by the dry combustion method. The differences in carbon stocks in various land uses were analyzed using Analysis of variance (ANOVA). Top soil layers (0-10cm) were found to store more carbon than the deeper ones. Furthermore, intact forest stored more soil organic carbon (> 45t/ha) compared to other land uses with the least in land under agriculture (about 1.5 t/ha). The decimation of land uses with high carbon stocks was noted to reduce the potential of Mt. Elgon as a carbon sink. This therefore calls for the scaling out and up of forest restoration programmes in and around mountain environments, whose success will depend on the active participation of all stakeholders including, Uganda Wildlife Authority (UWA), local communities, politicians and leaders.
Keywords: Land use change; Carbon stocks; Climate variability; Mt. Elgon; Eastern Uganda